2009
DOI: 10.1111/j.1399-0039.2009.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐23 receptor gene polymorphisms is associated with dilated cardiomyopathy in Chinese Han population

Abstract: Idiopathic dilated cardiomyopathy (DCM) is characterized by ventricular chamber enlargement and systolic dysfunction with normal left ventricular wall thickness. The pathogenesis of DCM has been extensively investigated for many years, but it remains uncertain. Recently, many studies indicated that autoimmune mechanisms are likely to participate in the pathogenesis of DCM. Interleukin-23 receptor (IL-23R) gene polymorphisms have been previously found to be associated with autoimmune diseases. To assess the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Similar to the IL-12 expression trends, circulating or cardiac IL-23 levels were found to be increased in patients with dilated cardiomyopathy, and with idiopathic dilated cardiomyopathy (Yi et al, 2009;Li et al, 2010;Myers et al, 2016). Individuals with IL-12, IL-23R polymorphisms, such as SNP rs10889677, are more susceptible to dilated cardiomyopathy among the Chinese Han population, rather than those with rs1884444 and rs11465817 (Chen et al, 2009). Elevated IL-27 mRNA levels were observed in the heart tissue of human dilated cardiomyopathy patients, and an IL-27 gene polymorphism involving SNP rs153109, rather than SNP rs17855750, predisposes to dilated cardiomyopathy in the Chinese Han population (Noutsias et al, 2011;Chen et al, 2017b).…”
Section: Interleukin-12 Family Members and Cardiomyopathymentioning
confidence: 55%
See 1 more Smart Citation
“…Similar to the IL-12 expression trends, circulating or cardiac IL-23 levels were found to be increased in patients with dilated cardiomyopathy, and with idiopathic dilated cardiomyopathy (Yi et al, 2009;Li et al, 2010;Myers et al, 2016). Individuals with IL-12, IL-23R polymorphisms, such as SNP rs10889677, are more susceptible to dilated cardiomyopathy among the Chinese Han population, rather than those with rs1884444 and rs11465817 (Chen et al, 2009). Elevated IL-27 mRNA levels were observed in the heart tissue of human dilated cardiomyopathy patients, and an IL-27 gene polymorphism involving SNP rs153109, rather than SNP rs17855750, predisposes to dilated cardiomyopathy in the Chinese Han population (Noutsias et al, 2011;Chen et al, 2017b).…”
Section: Interleukin-12 Family Members and Cardiomyopathymentioning
confidence: 55%
“…Aggravate Aggravate -- Zhu et al, 2013;Zhang et al, 2014b;Zhu et al, 2014;Hu et al, 2016;Liao et al, 2017; Shioi et al, 1997;Nishio et al, 2003;Fairweather et al, 2005;Yang et al, 2011;Jiang et al, 2014;Kong et al, 2014;Hu et al, 2014;Zhu et al, 2015;Sesti-Costa et al, 2017;Ouyang et al, 2017;Xu et al, 2018 Cardiomyopathy Aggravate Aggravate -- Afanasyeva et al, 2001;Fairweather et al, 2004;Sonderegger et al, 2006;Zafra et al, 2007;Chen et al, 2009;Noutsias et al, 2011;Wu et al, 2016;…”
Section: Cardiac Ischemia Reperfusionunclassified
“…modulation of SERCA activity, unknown roles for Ser10 phosphorylation [60,61] vinculin (Ser1033, Ser1045) modulation of lipid-docking [180] signaling β2-adrenergic receptor (β2-AR; Ser261, Ser262, Ser344, Ser345) modulation of adrenergic signaling & force generation [181] G-protein coupled receptor kinase (GRK2, Ser29; GRK5) enhances GRK activity, modulation of adrenergic signaling [182,183] histone deacetylase 5 (HDAC5; Ser259, Ser498) modulation of nuclear shuttling and transcriptional activity [34,184] signal transducer and activator of transcription 3 (STAT3, Ser727?) modulation of gene expression [88] protein phosphatase inhibitor-1 (IPP1; Ser67) modulates protein phosphatase-1 activity, indirectly influences PLN and SERCA activity [58] metabolism & mitochondria glyceraldehyde 3-phosphate dehydrogenase (GAPDH, Thr246) modulation of GAPDH-driven mitophagy in ischemia/reperfusion [185] subunit IV of the cytochrome c oxidase complex (COIV) modulation of COIV activity [186,187] Dynamin-Related Protein 1 (Drp1; Ser616) modulation of mitochondrial fission [188] pyruvate dehydrogenase kinase 2 (PDK2) modulation of enzyme activity [189] 6-phosphofructokinase-2 (PFK2, Thr475) modulation of enzyme activity [90] PKNs myofibrillar, cytoskeletal α-actinin 2 (ACTN2) unknown, potential regulation of actin cytoskeleton [104] β-adducin (ADD2) unknown, potential role in hypertension and dilated cardiomyopathy [105,190,191] α-B crystallin (CryAB) unkown, potential role during ischemia [95] signaling Focal adhesion kinase 1 (FADK1/PTK2) unknown, potential role for integrin signaling [105] G-protein coupled receptor kinase (GRK4) unknown, potential modulation of G-protein coupled receptor signaling [105] oxidative stress responsive kinase 1 (OXSR1/OSR1) unknown, potential role during cardiac development [105,192] serine/arginine-rich specific kinase 3 (SRPK3/STK23) unknown, potential role in ischemia and dilated cardiomyopathy [105,193,194] mammalian sterile 20-like kinase 1 (MST1/STK4) unknown, potential role in ischemia and a...…”
Section: Cardiac Rolesmentioning
confidence: 99%
“…In a cohort from Hungary, the AA genotype of rs10889677 represented a risk factor for rheumatoid arthritis (RA) (OR = 2.15) [8], However, another study revealed that A allele conferred a protective role for ankylosing spondylitis (AS) (OR = 0.81) [9]. Differently, some study demonstrated that wildtype C allele increased the risk to Graves' ophthalmopathy (GO) (OR = 2.03) [10] and idiopathic dilated cardiomyopathy (DCM) (OR = 1.694) [11].…”
Section: Introductionmentioning
confidence: 93%